Characteristics And Effects Of Acute Bronchiolitis In Infectious Children (Citomegalovirus) - Isanova Dilfuza Tursunovna (Genius Journals, 2023)
The article is dedicated to the problem of acute bronchitis in children. The relevance of this problem is obvious: according to conservative estimates, more than 150 million cases of bronchiolitis are registered annually.7-13% of these cases require hospital treatment and 1-3%-hospitalization in an ICU. The most common etiologic factor is the virus-respiratory synsytial (the vast majority of cases-60- 80%)cytomegalovirus, influenza viruses, parainfluenza, adenovirus, coronavirus are also important agents. A number of factors can cause the evolution of bronchiolitis in 0- 2 years-old children. Premature infants, children with bronchopulmonarydysplasia, bottle-fed children, and patients with congenital malformations and immunodeficiencies undergo bronchiolitis especially hard
Keywords: cytomegalovirus; influenza; parainfluenza